Smart home system based on IoT - Pavan Kumar, T; Hemanth krishna, R; Sai krishna, M; Meghana, Jhanavi (International Journal of Engineering and Technology, 2018)
In this era, IoT (Internet of Things) is the most emerging technology which is improving day-by-day. According to a survey the IoT growth will be from USD 170.57 Billion in 2017 to USD 561.04 Billion by 2022, at Compound Annual Growth Rate (CAR) of 26.9%. IoT is the smart technology which used to control the devices from anywhere we are. In this project we are going to discuss on how to control and provide security to our home appliances. There are many others ways to get control and othere security to our home appliances but we are trying to implement that by using our method. So, to provide security to our home appliance we are using a micro-controller, sensors, buzzer and a GSM module. The micro-controller is used to get control over the home appliances we are connected with and the sensors will give the information about what is happening over there, and if there is any threat the buzzer connected there will make the noise and makes alert and through the GSM module the information will be sent the registered mobile number. By, seeing this message will can get alert and provide security to our home appliances.